2011
DOI: 10.1177/230949901101900120
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Patient Information Sheets in Wrist Arthroscopy: A Randomised Controlled Trial

Abstract: Purpose. To evaluate the effects of perioperative information for wrist arthroscopy on postoperative pain, return to daily activities, and patient satisfaction. Methods. 34 women and 21 men aged 19 to 54 (mean, 35) years underwent diagnostic wrist arthroscopy to explore the radiocarpal and midcarpal joints. They were randomised to receive specific preoperative information on the procedure (pictures of the wrist joint anatomy, portal entry sites, and the arthroscope) and written instructions on postoperative ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In agreement, one study of total knee arthroplasty found that patients who received preoperative education reported being satisfied or very satisfied after the surgery more often than did controls [19]. These findings are consistent with the results of other studies that reported a high degree of postoperative satisfaction with pain management through a continuous quality improvement effort [17, 22].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In agreement, one study of total knee arthroplasty found that patients who received preoperative education reported being satisfied or very satisfied after the surgery more often than did controls [19]. These findings are consistent with the results of other studies that reported a high degree of postoperative satisfaction with pain management through a continuous quality improvement effort [17, 22].…”
Section: Discussionsupporting
confidence: 86%
“…Hence, it has been used in a number of clinical trials [15, 16]. A recent randomized trial reported that preoperative information was associated with less pain, reduced consumption of analgesics, and earlier return to daily activities after wrist arthroplasty [17]. Pain is a multidimensional experience that requires a multidimensional approach that includes drug treatment as well as behavioral preparation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Patient information leaflets, describing the procedure and postoperative care, may be useful in augmenting patient understanding, and also in reducing postoperative pain & facilitating earlier return to daily activities. 7…”
Section: Preoperative Planning and Consentmentioning
confidence: 99%
“…Makki and colleagues demonstrated that written postoperative instructions resulted in decreased discomfort, consumption of fewer analgesics and a more prompt resumption of regular activities [1]. In addition, studies have demonstrated that educational videos are beneficial in the improvement of melanoma awareness [2], promotion of sunscreen use [3] and facilitation of chronic disease management [4].…”
Section: Introductionmentioning
confidence: 99%